Rasionalitas Penggunaan Oains pada Pasien Osteoarthritis di Klinik Teluk Banten - Candra Junaedi; Santi Endrawati; Dimas Danang Indriatmoko; Muhamad Parci (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Osteoarthritis is a type of arthritis that occurs in the area around the joints because the cartilage that protects the ends of the bones begins to break down accompanied by reactive changes at the edges of the joints which can cause pain and difficulty moving. Drug use is said to be rational if the patient receives treatment that is in accordance with clinical needs, namely correct diagnosis, correct drug selection, correct indication, correct dose, correct method of administration, and correct patient. This research aims to use a descriptive analysis design for observational research. The research design used was quantitative research to determine the rationality of using NSAIDs anti-pain medication in osteoarthritis patients undergoing treatment at the Klinik Teluk Banten. The rationality results in this research are, 100% correct diagnosis, 100% correct indication. 100% correct choice of drug, 89% correct dose, 100% correct method of administration, 94% correct patient for Osteoarthritis at Klinik Teluk Banten.